2(w-1)=3(x-1)

Simple and best practice solution for 2(w-1)=3(x-1) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(w-1)=3(x-1) equation:


Simplifying
2(w + -1) = 3(x + -1)

Reorder the terms:
2(-1 + w) = 3(x + -1)
(-1 * 2 + w * 2) = 3(x + -1)
(-2 + 2w) = 3(x + -1)

Reorder the terms:
-2 + 2w = 3(-1 + x)
-2 + 2w = (-1 * 3 + x * 3)
-2 + 2w = (-3 + 3x)

Solving
-2 + 2w = -3 + 3x

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 2w = -3 + 2 + 3x

Combine like terms: -2 + 2 = 0
0 + 2w = -3 + 2 + 3x
2w = -3 + 2 + 3x

Combine like terms: -3 + 2 = -1
2w = -1 + 3x

Divide each side by '2'.
w = -0.5 + 1.5x

Simplifying
w = -0.5 + 1.5x

See similar equations:

| -3(a+2)=-26+a | | -4(-4+7v)-2=-7(1+3v) | | 5z+9=21 | | (9x+1)/(11x+5) | | 4x^3=x | | 14x-4=80 | | -4(7+7n)+6n=94 | | 2x=19.5 | | M-1.2=2.09 | | -5n=4(-1)+8 | | 2c-6=18 | | z+z-6-2=-2 | | h/18-16-14=24 | | 9x(2x-1)=5 | | 8(x+14)=192 | | -4(5-5x)=36-8x | | 7x-8x-8=x-11 | | 14+7+(-1)= | | 1/7n-5=80 | | 1/66+1/x=1/54 | | 14+19+x/3=17 | | 41+11+41+11=104 | | 0.45x+0.05(16-x)=0.10(32) | | x-(-7)=5 | | 40+55e=42+80e | | -9+8k=7+3k | | 3y=4y^2-1 | | -2(-7)+10w=34 | | 9*v+10=9*v+9 | | 21x=2 | | 3r+7(r+4)=7r+34 | | 2v+5-6v=13 |

Equations solver categories